1991
DOI: 10.1007/bf01000383
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin mRNA expression increases after corticospinal axotomy in the adult hamster

Abstract: We examined changes in vimentin gene expression during Wallerian degeneration after corticospinal axotomy in the adult hamster. Vimentin, which is the product of a type III intermediate filament (IF) gene, is expressed in various cells of mesenchymal origin, including microvascular endothelial cells, microglia and developing astrocytes. While increases in vimentin protein have been observed after various types of central nervous system (CNS) injury, it is not known whether this increase is due to increased vim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…A similar regulation of GF AP mRNA is also observed at distance from the lesion site, in the projection areas [40,41,51]. After injury, the 88 reexpression of VIM occurs in astrocytes close to the injury and at distance from the lesion site in a subset of astrocytes associated with Wallerian degeneration [7,29,44].…”
Section: Introductionmentioning
confidence: 72%
“…A similar regulation of GF AP mRNA is also observed at distance from the lesion site, in the projection areas [40,41,51]. After injury, the 88 reexpression of VIM occurs in astrocytes close to the injury and at distance from the lesion site in a subset of astrocytes associated with Wallerian degeneration [7,29,44].…”
Section: Introductionmentioning
confidence: 72%
“…Vim is the intermediate filament (IF) protein which is present in astrocytes early in development (Dahl et al, 1981) and is gradually replaced by GFAP as the main IF protein in astrocytes during maturation (Pixley and De Vellis, 1984;Stichel et al, 1991). Vim is usually undetectable in gray matter astrocytes of adult animals (see Khurgel et al, 1992), but it appears to be re-expressed in these cells following activation of astrocytes due to trauma (Calvo et al, 1991;Mikucki and Oblinger, 1991;Petito et al, 1990;Schiffer et al, 1986;Takamiya et al, 1988) or seizure activity (Khurgel et al, 1992(Khurgel et al, , 1995. Therefore, the presence of Vim+ astrocytes a t the site of vehicle injection (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Although GFAP has been a useful biomarker for assessing astrocyte reactivity to date, there remains an unmet need for better markers. Vimentin is another intermediate filament that expressed in astrocytes early in development, but appears to be gradually replaced by GFAP during development (62, 63). Recent transcriptomic studies have revealed some reactive astrocyte genes that might prove to be a better marker for assessing astrocyte reactivity (1).…”
Section: Reactive Astrocyte Induced By Traumatic Brain Injurymentioning
confidence: 99%